A family of genus‐specific RNAs in tandem with DNA‐binding proteins control expression of the badA major virulence factor gene in Bartonella henselae. Issue 2 (28th October 2016) - Tu, Nhan; Carroll, Ronan K.; Weiss, Andy; Shaw, Lindsey N.; Nicolas, Gael; Thomas, Sarah; Lima, Amorce; Okaro, Udoka; Anderson, Burt
Abstract: Bartonella henselae is a gram‐negative zoonotic bacterium that causes infections in humans including endocarditis and bacillary angiomatosis. B. henselae has been shown to grow as large aggregates and form biofilms in vitro. The aggregative growth and the angiogenic host response requires the trimeric autotransporter adhesin BadA. We examined the transcriptome of the Houston‐1 strain of B. henselae using RNA‐seq revealing nine novel, highly‐expressed intergenic transcripts ( Bartonella regulatory transcript, Brt1‐9). The Brt family of RNAs is unique to the genus Bartonella and ranges from 194 to 203 nucleotides with high homology and stable predicted secondary structures. Immediately downstream of each of the nine RNA genes is a helix‐turn‐helix DNA‐binding protein (transcriptional regulatory protein, Trp1‐9) that is poorly transcribed under the growth conditions used for RNA‐seq. Using knockdown or overexpressing strains, we show a role of both the Brt1 and Trp1 in the regulation of badA and also in biofilm formation. Based on these data, we hypothesize that Brt1 is a trans ‐acting sRNA that also serves as a cis ‐acting riboswitch to control the expression of badA . This family of RNAs together with the downstream Trp DNA‐binding proteins represents a novel coordinated regulatory circuit controlling expression of virulence‐associated genes in the bartonellae. Abstract : We describe a novel regulatory system that controls badA expression in Bartonella henselae . It includes a sRNA (Brt1) and a second RNA element controlling transcription of the downstream DNA‐binding protein (Trp1) that positively regulates badA . We hypothesize that this system coordinates badA expression and the associated biofilm formation.